Analisis Model Pendidikan Bagi Anak Abk (Anak Berkebutuhan Khusus): Homeschooling Dan Disleksia (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Children deserve decent education. In order to fit the best quality of education, every child has the opportunity to experience the proper method of learning considering his/her passions, talents, as well as actual conditions. This necessity is also a basic need for children with dyslexia. There are commonly three recommended education methods for children with special needs, i.e. sending the kids to special needs schools, choosing preferable inclusive schools and performing homeschools. Because dyslexia is a kind of learning disorder, parents of children with dyslexia often prefer homeschooling as a choice. This study aimed to describe how homeschooling could be an alternative for educating children with dyslexia. The researchers applied a literature approach using content analysis. The result showed that homeschooling could be an alternative of educational method for children with dyslexia.